Influence Of Mid-Cycle Pg Treatment And Gnrh At Ai On Plasma Minerals Profile In Conceiving And Non-Conceiving Repeat Breeding Crossbred Cows - Patel, K.R.; Dhami, A.J.; Savalia, K.K.; Hadiya, K.K.; Pande, A.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
This study was carried out in AMUL milk shed area on 30 crossbred cows, comprising 20 repeat breeding and 10 normal cyclic ones to evaluate their clinical response to mid-cycle PGF2α and AI + GnRH protocol (10 RB cows each) and to monitor plasma macro-micro minerals profile on day 0,7, 9 (AI) of treatment and on day 21 post-AI. Nine out of 10 cows exhibited estrus within 82.67±4.22 hrs of mid-cycle PGF2α (25 mg, i/m) treatment. The first service and overall conception rates of 3 cycles were 40 and 80 % in mid-cycle PGF2α group; 30 and 70 % in AI + GnRH (20 µg, i/m) group; and 50 and 80 % in normal cyclic control group. In normal cyclic control group, the overall mean values of plasma calcium, phosphorus and magnesium were 9.98 ± 0.04, 5.97 ± 0.10 and 3.14 ± 0.03 mg/dl, respectively. Almost same profile was observed for repeat breeders. The mean values of plasma zinc, iron, copper, cobalt and manganese concentration were 1.04 ± 0.03, 16.26 ± 0.31, 1.23 ± 0.03, 0.63 ± 0.03 µg/ml, and 0.19 ± 0.01 µg/ml, respectively. There is no significant difference observed in micro minerals profile among the animals under three groups, except zinc and copper, which were significantly (P
Keywords: Crossbred cows; Repeat breeding; Mid-cycle PG; AI GnRH; Fertility; Plasma minerals profile